2016
DOI: 10.1186/s12877-016-0358-3
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic and yet C. difficile-toxin positive? Prevalence and risk factors of carriers of toxigenic Clostridium difficile among geriatric in-patients

Abstract: Background Clostridium difficile infections (CDI) are the most frequent cause of diarrhoea in hospitals. Geriatric patients are more often affected by the condition, by a relapse and complications. Therefore, a crucial question is how often colonization with toxigenic Clostridium difficile strains occurs in elderly patients without diarrhoea and whether there is a “risk pattern” of colonized patients that can be defined by geriatric assessment. Furthermore, the probability for those asymptomatic carriers to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 44 publications
1
19
1
5
Order By: Relevance
“…The asymptomatic colonization rate of toxigenic C. difficile in hospitalized adult patients was found to range from 3% to 20%, but this is higher (24%–55%) in infants and young children …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The asymptomatic colonization rate of toxigenic C. difficile in hospitalized adult patients was found to range from 3% to 20%, but this is higher (24%–55%) in infants and young children …”
Section: Introductionmentioning
confidence: 99%
“…8 Furthermore, typing studies have found that only a small proportion of CDI is linked to nosocomial transmission. [9][10][11] The asymptomatic colonization rate of toxigenic C. difficile in hospitalized adult patients was found to range from 3% to 20%, [12][13][14][15] but this is higher (24%-55%) in infants and young children. 16,17 Children and adolescents undergoing therapy for cancer are at high risk for CDI due to exposure to several known CDI risk factors including profound myelosuppression and broad-spectrum antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…De plus, les patients à risque d'IAS sont souvent âgés et immunodéprimés, il peut ainsi s'avérer difficile d'atteindre une réponse immune protectrice. Par ailleurs, les agents infectieux responsables d'IAS sont souvent d'origine endogène, provenant de la flore commensale et/ou associés à un portage mais peuvent également avoir une origine exogène, résultant de la transmission croisée en milieu de soins [14][15][16][17][18]. L'utilisation de vaccins pour prévenir les IAS devrait ainsi être envisagée chez les patients pour les protéger d'agents infectieux dont ils sont porteurs.…”
Section: Mots Clésunclassified
“…Il s'agit d'une IAS par essence. C. difficile est principalement d'origine endogène [16], cependant, la transmission croisée manuportée via les soignants est possible [59]. Aux États-Unis, c'est la première cause d'IAS [3].…”
Section: Vaccins En Développementunclassified
See 1 more Smart Citation